Creciente y vaciante del Río Amazonas - (:unkn) unknown (My University, 1920)
Map of the Amazon River flood and trough, showing the flood of January, February, March, April, May, June, June, July, August, September, October, November, December, which occurred in 1920.

Mapa de Creciente y vaciante del Río Amazonas, en donde se muestra la creciente del mes de Enero, Febrero, Marzo, Abril, Mayo, Junio, Julio, Agosto, Setiembre, Octubre, Noviembre, Diciembre, que se dio en el año 1920
Amazon River swell and tidal wave
Keywords: Incluye: Meses de creciente y vaciante; Iquitos (Peru)--maps; Peru--cartographic materials; Peru--maps